Families of the Forest : The Matsigenka Indians of the Peruvian Amazon - Johnson, Allen W. (Book collections on Project MUSE., 2003)
The idea of a family level society assumes moving, breathing form in Families of the Forest. According to Allen Johnson's ethnography, the Matsigenka people of southeastern Peru cannot be understood or appreciated except as a family level society; the family level of sociocultural integration is for them a lived reality.